2020
DOI: 10.3389/fped.2020.00472
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Critical Care and the Climate Emergency: Our Responsibilities and a Call for Change

Abstract: Critical care is perhaps one of the most "climate-intensive" divisions of health care. As greenhouse gas emissions continue to rise, the unprecedented threat of climate change has belatedly prompted an increased awareness of critical care's environmental impact. Within our role as pediatric critical care providers, we have a dual responsibility not only to care for children at their most vulnerable, but also to advocate on their behalf. There are clear, demonstrable effects of our worsening climate on the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Of the included reviews, four were systematic reviews (Table 2) [21][22][23][24], three were technical and commissioned reports (Table 3) [13,25,26] and 16 were narrative reviews, or opinion pieces with substantive literature reviews (Table 4) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] All reviews and reports were published in international peer-reviewed journals with the exception of the Assembly of First Nations Report which was included as the challenges faced by indigenous children and their families are under-represented in the literature. Sixteen reviews The primary theme of interest in the scoping review was the association of climate change and child health inequalities reported in three specific dimensions; within country differences by social groups, between country differences (LMICs vs. HICs), and living in specific geographical locations.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included reviews, four were systematic reviews (Table 2) [21][22][23][24], three were technical and commissioned reports (Table 3) [13,25,26] and 16 were narrative reviews, or opinion pieces with substantive literature reviews (Table 4) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] All reviews and reports were published in international peer-reviewed journals with the exception of the Assembly of First Nations Report which was included as the challenges faced by indigenous children and their families are under-represented in the literature. Sixteen reviews The primary theme of interest in the scoping review was the association of climate change and child health inequalities reported in three specific dimensions; within country differences by social groups, between country differences (LMICs vs. HICs), and living in specific geographical locations.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Of the included reviews, four were systematic reviews (Table 2) [21][22][23][24], three were technical and commissioned reports (Table 3) [13,25,26] and 16 were narrative reviews, or opinion pieces with substantive literature reviews (Table 4) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. All reviews and reports were published in international peer-reviewed journals with the exception of the Assembly of First Nations Report which was included as the challenges faced by indigenous children and their families are under-represented in the literature.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate change is a striking example of a global threat that is anticipated to affect human health in multiple ways, and there are clear implications for critical illness. [3][4][5][6][7] Cardiac, pulmonary, and renal conditions can be worsened by heat stress, and the dangers are worse for older adults, children, and socioeconomically disadvantaged people. Climate change is expected to exacerbate both natural disasters and infectious diseases, with subsequent associated health problems.…”
Section: Bedside To Worldwidementioning
confidence: 99%